The Influence of Live Streaming Video on Consumer Decisions - I Gusti Ayu Oka Netrawati; I wayan Nuada; Baehaki Syakbani (Universitas Muhammadiyah Sorong, 2022)
This study aims to determine whether Instagram live streaming has an impact on consumer decisions. live streaming and purchasing decisions are variables used in this study to determine the relationship between these two variables by regression analysis with SPSS. Questionnaires were distributed to 100 respondents who are followers of Nhalombok and who made purchases during the live streaming. The results of the study indicate that there is a dominant influence of the live steaming variable on consumer decisions. The coefficient of determination shows that the live streaming variable affects consumer decisions.